Implementation of Decentralization Policy in Improving Public Health Services in Urban Areas - Anastasya, Suci; Rahman, Arif (IHSA Institute, 2025)
Decentralization has become a key policy approach for improving public health services by granting local governments greater autonomy in decision-making and resource allocation. This research examines the implementation of decentralization policy in enhancing healthcare services in urban areas, analyzing its benefits, challenges, and impact on governance efficiency. Using a mixed-methods approach, including policy analysis, case studies, and stakeholder interviews, the study evaluates the effectiveness of decentralized healthcare systems in addressing urban health disparities. The findings reveal that decentralization improves service accessibility, responsiveness, and efficiency by allowing municipal authorities to tailor healthcare initiatives to local needs. Additionally, the integration of digital health technologies, such as telemedicine and electronic health records, has strengthened decentralized healthcare delivery. However, financial disparities between municipalities, weak intergovernmental coordination, and inconsistencies in crisis response pose significant challenges to policy effectiveness. Comparing these results with previous research, this study confirms decentralization’s role in improving healthcare outcomes while highlighting the need for stronger fiscal redistribution mechanisms, enhanced governance structures, and digital health integration. To optimize decentralized healthcare governance, the study recommends targeted financial support for underfunded areas, improved coordination between national and local health agencies, and the expansion of technology-driven healthcare solutions. This research contributes to the ongoing discourse on decentralized governance by providing policy-oriented solutions to enhance healthcare equity and efficiency in urban settings. Future research should explore long-term policy impacts and innovative strategies to address persistent challenges in decentralized healthcare systems.